Pengaruh Cita Rasa, Harga Produk dan Promosi Penjualan Sosial Media terhadap Keputusan Pembelian Kopi Janji Jiwa di Cikarang Selatan - Intania Putri Nurcahyani; Yos Soejarminto (SAFE-Network, 2023)
This is a change in the lifestyle of the Indonesian people who increasingly prefer drinking coffee in coffee shops. Coffee is no longer just a drowsiness reliever, but as part of a lifestyle where coffee shops are a very popular place. This study aims to determine the effect of taste, product price and social media sales promotion on purchasing decisions of West Cikarang coffee consumers. Competition between coffee shops is getting tougher, so that consumers will be more careful and selective when faced with various choices of places. This study aims to examine the effect of taste image on consumer purchasing decisions, this study also aims to examine the effect of product prices on purchasing decisions and this study aims to examine the effect of social media sales promotions on purchasing decisions and this study also aims to examine the effect of taste image, product prices and social media sales promotion on purchasing decisions of consumers of Janji Jiwa coffee consumers in South Cikarang. The sampling method used is non probability sampling with a purposive sampling method with a sample of 100 respondents. The sample in this study is the entire community in South Cikarang. This study used SPSS software version 25. The analytical method used was Validity Test, Reliability Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test, Autocorrelation Test, Multiple Linear Regression Test, T Test, Coefficient of Determination Test. Taste has a positive and significant influence on the purchasing decision of Janji Jiwa Coffee; Product Price has a positive and significant influence on the purchasing decision of Janji Jiwa Coffee; Sales Promotion which has a positive and significant influence on the purchasing decision of Janji Jiwa Coffee; Taste, product price and sales promotion all three have a positive and significant influence on purchasing decisions.